A random-walk benchmark for single-electron circuits - David Reifert (Nature Portfolio, 2021)
Fidelity control is important to quantum metrology and fault-tolerant quantum computation. Here, authors realize clock-controlled transfer of electrons through quantum dots and describe the statistics of accumulated charge by a random-walk model, achieving a benchmark for single-electron circuits.